MACRONUTRIENT DEFICIENCY AND ITS EFFECT ON BLOOD BIOCHEMICAL COMPOSITION AND ANTHROPOMETRIC INDICATORS - Chuliyeva Muxayyo Azam Qizi (Scholar Express Journals, 2022)
In the article problems related to healthy eating of a group of four-year-old children are mentioned. The deficiency of macronutrients in children's food is reflected in their blood biomarkers. The reason for deviations from the norm determined in the biochemical analysis of blood, in turn, was assessed as a lack of macronutrients in the food. The reduction of macronutrients and proteins in the blood caused a decrease in the height and weight of children is evaluated through correlational relationships.
Keywords: Protein; macronutrient,; healthy eating